The demiurge in the convex mirror. The Hermetic keys of Parmigianino’s Self-Portrait in a Convex Mirror - Ferrer-Ventosa, Roger (Eikón / Imago, 2024)
The article analyses the conceptual foundations of Parmigianino in relation to his Hermetic and Neoplatonic ideas and alchemical practice, which were important in Renaissance Italian culture. Parmigianino’s Self-Portrait in a Convex Mirror is viewed as an embodiment of the artist as a demiurge, a creator of a brand new universe. The article highlights the symbolic and metaphysical significance of the convex mirror, reflecting the artist’s creative power and the hidden values of reality. Melancholy, associated with Saturn, was a characteristic of artists and intellectuals in that cultural context. The article discusses Parmigianino’s frescos of Diana and Actaeon, a myth that symbolizes the pursuit of wisdom and the transformative process of the alchemist. Finally, it is also examined Parmigianino’s potential interest in alchemy based on historical accounts. The controversy surrounding Parmigianino’s involvement in alchemy is discussed, along with the opinions of various scholars